Influence of sodium nitrite on protein oxidation and nitrosation of sausages subjected to processing and storage. (June 2016) - Feng, Xianchao; Li, Chenyi; Jia, Xu; Guo, Yan; Lei, Na; Hackman, Robert M.; Chen, Lin; Zhou, Guanghong
Abstract: The influence of NaNO2 content on protein oxidation and nitrosation was investigated in cooked sausages at different concentrations (0, 50, 100, 200 and 400 mg NaNO2 /kg). Dependent on concentration, NaNO2 had both anti- and pro-oxidant effects on protein oxidation. The antioxidant effects of NaNO2 on the protein oxidation were evidenced by significantly lower carbonyl contents, higher free amines and lower surface hydrophobicities. The pro-oxidant effects of NaNO2 on protein oxidation resulted in a decrease of sulfhydryls and an increase of disulfide bonds. NaNO2 also improved the protein nitrosation inducing the formation of 3-nitrotyrosine (3-NT). Moreover, 3-NT had significant correlations with parameters of protein oxidation, indicating that 3-NT may be a possible marker for protein oxidation. Results of this study contribute to an understanding of the impact of NaNO2 on food quality and help to identify optimal formulations of cured meat products. Highlights: Nitrite had both anti and pro-oxidant effects on protein oxidation in cooked sausages. Nitrite can prevent the conversion of free amines into carbonyls. Nitrite can promote the conversion of thiol groups into disulfide cross-links. Nitrite can enhance the protein nitrosation in cooked sausages. 3-Nitrotyrosine could be a promising marker for protein oxidation.